Analisis pengaruh bahan dasar terhadap indeks viskositas pelumas berbagai kekentalan - Rini Siskayanti; Muhammad Engkos Kosim (Jurnal Rekayasa Proses, 2017)
Lubricants are chemicals, which are generally liquid, provided between two moving objects to reduce frictional forces. The lubricant is made from a 70-90% base oil mixture and added with an additive to enhance its properties. Basic lubricants can be grouped into 3 ie mineral lubricants, vegetable lubricants and synthetic lubricants. One of the functions of lubricants is as an engine coolant from heat arising from friction and sealing. Lubricant resistance to temperature changes is strongly influenced by the type of lubricant base material. The purpose of this research is to know the influence of basic material of lubricant to temperature change as measured by Viscosity Index value. Research done by making machine lubricant with various viscosity with addition of same additives, only kind of lubricant that used different but still refers to standard lubricant characteristic tested. Of 5 samples tested were DEO API CI-4 SAE 15W-40, API PCMO SN SAE 10W-40, API MCO SL SAE 10W-30, HO ISO VG 32, TO API TO-4 SAE 10W showed that lubricant using materials Synthetic foundations have higher viscosity index values than minerals (13-30% higher). This indicates that the quality of lubricants is also getting better.